Acute Ophthalmoplegia; Same Disease, Different Variants: Anti GQ1b Antibody Syndrome - Senem Ayça; Anna Carina Ergani; Muzaffer Polat (Galenos Yayinevi, 2018)
Patients with Miller Fisher syndrome (MFS) are characterized by acute ophthalmoplegia (AO) and areflexia. MFS is an immune mediated process, triggered by an infection and includes incomplete forms, such as ophthalmoplegia, ataxia and a central nervous system subtype known as Bickerstaff brainstem encephalitis (BBE). We present two cases admitted to our hospital on the same day. The first case was presented as AO, with elevated levels of anti GQ1b. The second case was presented as AO, oropharyngeal palsy and sensory motor polyneuropathy with borderline levels of anti GQ1b, diagnosed as BBE. There are atypical forms of MFS with different clinical symptoms and elevated levels of antibodies called "Anti GQ1b Antibody syndrome". The cases of the two patients diagnosed as MFS variants' AO and BBE.